Orthogonal strategy for the synthesis of dual-functionalised β3-peptide based hydrogels. Issue 34 (5th April 2016) - Kulkarni, Ketav; Motamed, Sepideh; Habila, Nathan; Perlmutter, Patrick; Forsythe, John S.; Aguilar, Marie-Isabel; Del Borgo, Mark P.
Abstract : We describe a new class of hydrogelator based on helical β 3 -peptide foldamers carrying a bioactive payload. The β 3 -peptides self-assemble to form a nanofibrous mesh resulting in a stable hydrogel. Co-incubation with different β 3 -peptide monomers allowed tuning of cell adherence. Abstract : We have described a new class of hydrogelator based on helical β 3 -peptides carrying a bioactive payload. The β 3 -peptides self-assemble in aqueous solution to form a nanofibrous mesh resulting in a stable hydrogel. The simple design provides the versatility for attaching different functional payloads to the β 3 -peptide scaffold to develop new materials.